The Implementation of Good Governance in the Presidential Election in Indonesia - Dian Fitri Sabrina; Rosa Ristawati (Universitas Airlangga, 2021)
The 2019 presidential and vice-presidential elections in Indonesia had complicated issues, including broken ballots, multiple voter lists, persons not registered as permanent voters, political money, transparency, administrative violations, electoral penalties and high white numbers. These problems indicate that the values of good governance have not been implemented in the election process. This paper uses the normative method to analyse the issues and laws, particularly when related to aspects of law enforcement and administrative law in good governance. This paper aims to formulate a method for implementing good governance in the election process. The results of the analysis show that electoral justice is very important in Indonesian presidential elections. However, the Indonesian presidential election system does not use good governance and does not support electoral justice. The results of previous elections in Indonesia showed that the values of good governance have not been well implemented in all stages of the election, especially regarding legal principles. This research proposes a good governance system to implement in the Indonesia presidential election process.